Investigation of balanced chromosomal aberrations prevalence in healthy Turkish Cypriot couples - Deryali, Dize; Cobanogullari, Havva; Ergoren, Mahmut Cerkez (Keai Publishing Ltd, 2025)
Chromosomal abnormalities play a significant role in reproductive issues and developmental disorders, yet information on their prevalence within the Turkish Cypriot population is limited. This study offers the first comprehensive cytogenetic evaluation of balanced chromosomal aberrations in 100 healthy Turkish Cypriot individuals of reproductive age. Structural abnormalities were detected in 4 % of participants, all of whom were female, including inversions, insertions, balanced translocations, and a derivative chromosome 22. The frequency of balanced translocations in this group was higher than global averages, highlighting important reproductive considerations for carriers. The observed sex-specific difference points to a complex interplay of genetic and epigenetic factors influencing chromosomal variation. To achieve accurate diagnosis and effective management, advanced molecular cytogenetic methods should be used alongside traditional karyotyping. Larger studies, especially those including male subjects, are needed to confirm these results and improve genetic counseling, risk assessment, and fertility treatment approaches tailored to this distinct population.
Keywords: Chromosomal abnormalities; Karyotyping; Cytogenetic analysis; Balanced translocations; Turkish Cypriot population